A Checklist of Canadian Literature and Background Materials 1628-1960 - Watters, Reginald Eyre 1912-1979 (Heritage, 2019)
This revised and enlarged Checklist provides as complete a record as possible of the separately published works that constitute the literature of English-speaking Canada up to 1960. Its purpose is to stimulate interest and research in our literary culture, to reveal individual figures and areas of investigation rich in published material, and to facilitate the finding of the books concerned. Background materials are included because the cultural soil must be known if a nation's belles-lettres are to be adequately studied or fully appreciated. Part I of the Checklist records all known titles in poetry, fiction, and drama that were produced by English-speaking Canadians. Part II is a selective listing of books by Canadians which will be of value to anyone studying the literature of culture of Canada. Here are included books of biography, literary criticism, scholarship, local history and religion. Each title published before 1951 is coded to indicate where copies of the book can be found. Some 16,000 titles by 7,000 Canadian authors are included in this comprehensive bibliography. This edition maintains the qualities that made the first edition an indispensable reference work for librarians, book collectors, book dealers, and scholars